Increasing Knowledge of Class VI Elementary School Students About the Dangers of Rheumatoid Arthritis (RA) at Public Elementary School 106830 Sidodadi Ramunia Village Lubuk Pakam - Pitriani, Pitriani; Purba, Anita Sri Gandaria; Fahlevi, Reza; Lubis, Yuni Suharnida; Sirait, Syah Fara Dillasani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
As a persistent systemic inflammatory condition, rheumatoid arthritis is the primary manifestation of which is increasing polyarthritis and affects Each and every organ of the human physique. Individuals World Health Organization experience Symptoms of rheumatoid arthritis will appear, namely blockage, tight joints, and inflammation of joint movement, occurrence of cutaneous nodules above which may feel bloated and warmer, which can impact the elderly's ability to perform their everyday activities. Volunteering in the community is essential. in attempts to raise awareness of Rheumatoid Arthritis. Community service was completed. on 50 Students at SD Negeri Elementary School in grade 6 106830 Sidodadi Ramunia Lubuk Pakam Village. The purpose of this exercise is to help pupils become more conscious of the need for knowledge about treating Rheumatoid Arthritis by doing rheumatic exercises that are practiced throughout the school. The reason for this behavior is outreach as well as public initiatives, where PkM may raise awareness of the benefits of doing rheumatic exercises for Rheumatoid Arthritis patients. Evaluation of this activity was carried out through a review activity by asking students questions regarding the meaning, signs and symptoms as well as treatment for Rheumatoid Arthritis patients. This PkM's findings demonstrate that knowledge and efforts have significantly increased. to treat rheumatic diseases at SD Negeri 106830, Sidodadi Ramunia Village, Lubuk Pakam. Students are expected to be able to practice rheumatic exercises at school and at home.